Dance critique as signature pedagogy. (July 2017) - Kearns, Lauren
The curriculum of preprofessional university degree programs in dance typically comprise four components: theory and history, dance technique, creative process, and performance. This article focuses on critique in the modern dance technique and choreography components of the dance curriculum. Bachelor of Fine Arts programs utilize critique as a signature pedagogy because "pedagogies must measure up to the standards not just of the academy, but also of the particular professions" (LeeShulman, 2005 ). Critique is an essential pedagogy in the training of dance artists and is a vital component of the dance field, as it facilitates an intellectual and kinesthetic deepening of the student's engagement with the dance profession.